]PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR ATLETIK ( LARI 100 M ) PADA PESERTA DIDIK - Ramdhani, Wardy; Simanjuntak, Victor; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research is, is there any influence of audio visual media to Athletic learning result. The purpose of this research is to find out the influence of audio visual media to athletic learning result (running 100m) on the 11th grade students of SMA Muhammadiyah Pontianak. The population of this research was 11th grade students, and it divided into 6 class with the total number of 240 students. The sample of this research was 40 student, taken by cluster random sampling technique. And the method of this research is True-experimental design, the data were analyzed using computerized and T-test. Based on the T-Test to experiment class, the value of t-test is -4486 and t-table is 2.0930, it showed that the mean of t-test of running 100m is t-test<t-table.  It means that Ho is rejected where is the improvement conventional method is 14,59 and using audiovisual method is 22.09.   Keywords : Audio visual media  and result of learning to run 100 m